Not so monochromatic: Size-dependency of both sex and color in the cleaner wrasse Labroides dimidiatus - Trigo, Sandra; Narvaez, Pauline; Cardoso, Gonçalo C.; Soares, Marta C. (Frontiers in Ecology and Evolution, 2023)
In marine interspecific cleaning mutualisms, small fish known as “cleaners” inspect the surface, gills and sometimes the mouth of ‘‘client’’ reef fish, eating ectoparasites, mucus, scales and dead or infected tissue. These cleaner fish species share similar vivid coloration that makes them recognizable by clients. To gain insight on additional communication roles of cleaner fish color, we tested if differences in color among cleaner wrasse Labroides dimidiatus individuals captured from the wild are explained by sex, body size or parasite loads. We found that males were larger, heavier and tended to have more saturated blue tails than females. We also found blue color saturation to be positively correlated with size, and that this size-dependence explains the trend for the sexes to differ in color. Parasite loads did not predict individual differences in color, but fish in our sample were not heavily parasitized. Other color traits (including yellow color saturation and black color brightness) did not differ between the sexes and were associated with morphological differences. Size-dependence of blue color may thus suggest that it is a condition-dependent signal that could be used in various types of inter- and intraspecific social interactions.